2012
DOI: 10.1007/s12664-012-0258-1
|View full text |Cite
|
Sign up to set email alerts
|

Survey of inflammatory bowel diseases in India

Abstract: The present survey provides a reasonable picture of the demographic features and clinical manifestations of Indian patients with IBD, their risk factors, course of disease, and the treatment given to them.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

15
108
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 91 publications
(125 citation statements)
references
References 31 publications
15
108
2
Order By: Relevance
“…Later studies from India indicated that 62 of 200 CD patients (31 %) in one series and 61 of 223 patients (27.4 %) in another had extraintestinal manifestations [16,17]. The Indian Society of Gastroenterology-Inflammatory Bowel Disease (ISG-IBD) Task Force in its survey of 409 patients with CD found that more than half of the patients (59 %) had extraintestinal symptoms [18]. In many Indian studies, Barthralgia^has been counted as Barthritis^without documentation and this very likely has increased the prevalence of extraintestinal manifestations dramatically.…”
Section: The Prevalence Of CD In Indian Immigrants To Developed Countmentioning
confidence: 99%
See 2 more Smart Citations
“…Later studies from India indicated that 62 of 200 CD patients (31 %) in one series and 61 of 223 patients (27.4 %) in another had extraintestinal manifestations [16,17]. The Indian Society of Gastroenterology-Inflammatory Bowel Disease (ISG-IBD) Task Force in its survey of 409 patients with CD found that more than half of the patients (59 %) had extraintestinal symptoms [18]. In many Indian studies, Barthralgia^has been counted as Barthritis^without documentation and this very likely has increased the prevalence of extraintestinal manifestations dramatically.…”
Section: The Prevalence Of CD In Indian Immigrants To Developed Countmentioning
confidence: 99%
“…The data collected by the ISG-IBD Task Force on 409 patients with CD showed that 4.6 % of them reported a definite diagnosis of IBD in at least one other member of their family [18].…”
Section: The Prevalence Of CD In Indian Immigrants To Developed Countmentioning
confidence: 99%
See 1 more Smart Citation
“…Of 409 cases of CD, more than 50 % were reported from southern India. However, an equivalent number of ulcerative colitis cases were reported from northern as well as southern India [4]. This is an exciting geo-epidemiological observation as it rebels against two traditional concepts of IBD epidemiology: the North-South divide [5] and interval emergence of ulcerative colitis (UC) and Crohn's disease.…”
mentioning
confidence: 99%
“…And after an inordinate delay that now seems acceptable we have the tortoise reaching the finish line with 2 publications in its basket: its report, and consensus statements and guidelines! [3,4].…”
mentioning
confidence: 99%